2003
DOI: 10.1111/j.1651-2227.2003.tb00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lactate and plasma volume recovery in adults and children following high‐intensity exercises

Abstract: Aim: To compare plasma lactate concentration recovery kinetics when measured and corrected for variations in plasma volume between children and adults. Methods: Nine boys (11.3 AE 1.1 y) and 8 men (21.9 AE 1.9 y) performed a maximal and a supramaximal exercise until exhaustion. Plasma lactate concentrations, haemoglobin and haematocrit were measured at rest, immediately on completion of exercise and after the 2nd, 5th, 12th and 30th minute of recovery. The plasma lactate concentrations and the rate of recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 19 publications
2
23
0
1
Order By: Relevance
“…The effects of higher lactate concentration in limiting exercise performance during an intense intermittent exercise shown by Ahmaidi et al (1) are largely confirmed by other literature studies (4,17,19,5,25). We supposed in the present study that the lower blood lactate concentration associated with the higher HR and higher oxygen uptake values in SR could be the factors in favor of the higher time limit exercise duration obtained for SR compared with AR and PR ( Figure 5).…”
Section: Discussionsupporting
confidence: 61%
“…The effects of higher lactate concentration in limiting exercise performance during an intense intermittent exercise shown by Ahmaidi et al (1) are largely confirmed by other literature studies (4,17,19,5,25). We supposed in the present study that the lower blood lactate concentration associated with the higher HR and higher oxygen uptake values in SR could be the factors in favor of the higher time limit exercise duration obtained for SR compared with AR and PR ( Figure 5).…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, capillary density has been shown in animals to decrease during maturation, i.e., as the fiber cross-sectional area increases with respect to growth (58,62,63). A higher functional capillarization would also explain the faster lactate clearance previously reported after exercise (4,6,12,22).…”
Section: Discussionmentioning
confidence: 92%
“…LP20, type LPG 344). A delay of 3 min was chosen since peak lactate concentrations are generally achieved between 2 and 5 min (Berthoin et al 2003). The whole blood that had been collected was placed in a flask containing anticoagulant.…”
Section: Blood Lactate Concentrationmentioning
confidence: 99%